Keterkaitan Undang-undang Pokok Agraria dengan Revitalisasi Pertanian - Sutarto, Sutarto (Caraka Tani: Journal of Sustainable Agriculture, 2006)
Revitalization in not retorika. Destination of agricultural revitalization is farming development. And farming development requires farming economic growth and structural change. Both are necessary to increase the national income and to create employment opportunities. However, economic growth and structural change would be materialized smoothly if, only if, its development was based on an agricultural development and the management of agrarian objects. So that must optimally manage allocation, the stock employment and the maintenance of the agrarian objects for the present generation as well as the future in order to achieve the prosperous society. Hopefully, the agrarian objects can be optimally managed and used for the present and future generation to reach the prosperous society.